2013
DOI: 10.1016/j.nicl.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged febrile seizures cause reversible reductions in white matter integrity

Abstract: Prolonged febrile seizures (PFS) are the commonest cause of childhood status epilepticus and are believed to carry a risk of neuronal damage, in particular to the mesial temporal lobe. This study was designed to determine: i) the effect of prolonged febrile seizures on white matter and ii) the temporal evolution of any changes seen.33 children were recruited 1 month following PFS and underwent diffusion tensor imaging (DTI) with repeat imaging at 6 and 12 months after the original episode of PFS. 18 age-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
(48 reference statements)
2
18
0
Order By: Relevance
“…We note from our short‐term follow‐up study that FA decreased at 1 month and 6 months post‐PFS and then normalized at 1 year with no evidence for FA increases as observed here 13. Similarly, AD was decreased at 1 and 6 months post‐PFS with no evidence for AD increases as observed in the present study.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We note from our short‐term follow‐up study that FA decreased at 1 month and 6 months post‐PFS and then normalized at 1 year with no evidence for FA increases as observed here 13. Similarly, AD was decreased at 1 and 6 months post‐PFS with no evidence for AD increases as observed in the present study.…”
Section: Discussionsupporting
confidence: 71%
“…A longitudinal study design could have provided a better description of the evolution of WM diffusion changes following PFS. We, nonetheless, have referred to the results from our previous study on a comparable cohort, but with a shorter follow‐up, to complement our data and interpret the findings 13. A possible limitation of TBSS is misregistration of individual scans to the common template for group analysis, which may be an issue particularly for structurally abnormal conventional scans.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Non-epilepsy children with CSE were younger at testing (p<0.001) and the epilepsy CSE group had lower Full-scale IQ (p<0.001) in comparison with the control and the nonepilepsy CSE groups. A multivariate analysis of variance with age at test and Full-scale IQ as covariates and SDQ, ASSQ, and SNAP-IV scores as dependent variables revealed a significant effect of Full-scale IQ (F [3,74] =11.05; p<0.001) and a trend for an effect of group (F [3,75]=2.6; p=0.067) on behavioural scores. Pairwise comparisons revealed a trend for a difference between the nonepilepsy CSE and the control group on the SDQ scale (F [2,76]=3.07; p=0.063).…”
Section: Questionnaire Results Compared With Population Norms and Conmentioning
confidence: 99%
“…Although animal studies support the hypothesis that a decrease of AD reflects axonal injury, studies on humans report inconclusive results. Some studies found an AD decrease, for example, following ischemic stroke or prolonged febrile seizures, whereas others report an AD increase, for example, in multiple sclerosis or idiopathic epilepsy syndromes in children . Hence, the nature of AD changes seems to be complex in humans and an increased AD (along with increased MD and RD) may reflect decreased tissue density, reflecting cell loss of both neurons and glia.…”
Section: Discussionmentioning
confidence: 99%